2007
DOI: 10.1016/j.neuroscience.2007.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Androgen and estrogen receptor–mediated mechanisms of testosterone action in male rat pelvic autonomic ganglia

Abstract: Although male reproductive function is primarily androgen dependent, many studies suggest that estrogens have direct actions on the male reproductive organs. Pelvic autonomic neurons provide the motor control of the internal reproductive organs and the penis and various properties of these neurons are affected by endogenous androgens. However, the possible role of estrogens at this site has not been examined. Here we have investigated the significance of estrogens produced by aromatisation of testosterone in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 58 publications
2
37
0
Order By: Relevance
“…Moreover, T can affect UB detrusor muscle contraction by neuronal regulation (Keast 1999;Hall et al 2002;Purves-Tyson et al 2007). Androgen deprivation apparently down-regulated the activity and expression of enzymes controlling the cholinergic as well as noncholinergic nerve functions (Filippi et al 2007;Juan et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, T can affect UB detrusor muscle contraction by neuronal regulation (Keast 1999;Hall et al 2002;Purves-Tyson et al 2007). Androgen deprivation apparently down-regulated the activity and expression of enzymes controlling the cholinergic as well as noncholinergic nerve functions (Filippi et al 2007;Juan et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the transcriptional activity of the tyrosine hydroxylase gene is transactivated by androgen receptors in a ligand-dependent manner [32]. Yet the fact that oestrogen response elements are also present and considering aromatase expression in ganglionic neurons [33] allows hypothesizing that androstenedione may be converted to oestradiol in the ganglion compartment before regulating the tyrosine hydroxylase gene. We however could not find differences among the levels of oestradiol in the incubation media of the ganglion compartment before and after stimulation with androstenedione (results not shown) suggesting that it is likely an effect of androstenedione per se and not mediated by its previous aromatization to oestradiol . We have shown that androstenedione impacts the CG and modulates steroidogenesis in the ovary increasing norepinephrine and decreasing nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen receptors are also located on both small and large primary afferent dorsal root ganglion nerves [106]. In addition to acting on androgen receptors, testosterone has also been converted to estrogen via aromatase present in the ganglionic neurons [107]. Estrogen receptors have been co-localized to PG neurons staining positive for neuronal nitric oxide synthase (nNOS) and tyrosine hydroxylase.…”
Section: Autonomic Input and Testosterone: Johanna L Hannan Carol Amentioning
confidence: 99%